Performance Analysis and Comparison of Symmetrical and Asymmetrical Dual Stator Induction Generators for Wind Energy Conversion Systems - Singh, R.; Verma, V. (Engineering, Technology & Applied Science Research, 2018)
The emergence of micro/nano level wind generation has opened the research on induction generator (IG) topologies having easier and finer control available in multiphase generators. To establish the suitability of multiphase generators for wind generators the analysis of their performance based on the developed model for the same rating of six phase symmetrical (60˚) and asymmetrical (30˚) IGs is presented. A comparative performance evaluation of grid-excited six phase symmetrical and asymmetrical IGs also known as Dual Stator Induction Generators (DSIGs) is presented through simulation results in MATLAB/SIMULINK environment amidst load perturbations, limited variation of wind speed and perturbations in voltage and frequency of the non stiff micro-grid to which they are connected. Based on the performance indices like flux of direct and quadrature axis, speed variations, terminal voltage drop/rise, range of operational speed variation etc., a comparative analysis with the help of the results is drawn to establish the suitability of asymmetrical multiphase IGs for grid connected wind generators.